IMPACT OF CALORIC VESTIBULAR STIMULATION ON CO-ORDINATION IN PARKINSON DISEASE INDUCED MICE - MOHAN, RAM; KAYALVIZHI,; RAMANATHAN, RASHMI; SHANMUGAM, JEEVITHAN; R., ARCHANA (International Journal of Pharmacy and Pharmaceutical Sciences, 2022)
Objective: This study was undertaken to evaluate the effect of vestibular stimulation on motor coordination in Parkinson’s disease (PD) induced mice. Methods: 18 healthy adult male Swiss albino mice were used in this study. Vestibule was stimulated by caloric vestibular stimulation (CVS). Pesticide Rotenone was used to induce Parkinson’s disease (PD). Motor coordination was assessed by the fall-off time and the activity score using the rotarod and actophotometer, respectively. Results: In the rotarod test, there was a significant increase in the fall-off time (p<0.01) in the CVS PD group (131.63±18.34) on the 30th day when compared to the PD group (95.33±15.17). In the actophotometer, the activity score improved in the PD CVS group on the 15 (235±47.09) and 30th days (251.38±25.76), while there was no improvement in the PD group. This shows the significant effect of caloric vestibular stimulation on motor coordination in Parkinson’s disease. Conclusion: This study confirms that caloric vestibular stimulation with hot water resulted in the improvement of motor coordination in PD. Hence this study certainly merits further studies with a higher sample size to confirm the effect of caloric vestibular stimulation on the enhancement of motor coordination in individuals with Parkinson’s disease.